International financial reporting standard: basic concepts (XBRL) of the eXtensible Business Reporting Language - Zasukhin K. A., Mikhnev I. P. (Science and education: future development, 2018)
This article discusses the basic concepts of an extensible business reporting language (XBRL). The international experience of application, functionality of XBRL is presented and the comparative analysis of realization XBRL by means of the software in the different countries is given.
Keywords: международные стандарты; international standards; язык деловой отчетности; бизнес-системы; язык разметки XML; консорциум всемирной паутины; формат отчетных данных; language of business reporting; business system; XML markup language; consortium of the World Wide Web; format of the reporting data